Aceh Free Pasung: Releasing the mentally ill from physical restraint - Marthoenis M; Puteh Ibrahim; Minas Harry (International Journal of Mental Health Systems, 2011)
Abstract Background Physical restraint and confinement of the mentally ill (called pasung in Indonesia) is common in Aceh. In early 2010, the local government initiated a program called Aceh Free Pasung 2010. The main goal of the program is to release the mentally ill in the province from restraint and to provide appropriate medical treatment and care. The aim of the paper is to report the findings of a preliminary investigation of the demographic and clinical characteristics of patients who have been admitted to the Banda Aceh Mental Hospital as part of the Aceh Free Pasung program. Methods This is a cross-sectional descriptive study conducted at the Banda Aceh Mental Hospital, where people who had been restrained or confined in the community are being admitted for psychiatric treatment and, where necessary, physical rehabilitation, as part of the Aceh Free Pasung program. Results Fifty-nine of former ex-pasung patients were examined. The majority (88.1%) of the patients were male, aged 18 to 68 years. The duration of pasung varied from a few days to 20 years, with a mean duration of 4.0 years. The reasons for applying pasung are many, with concerns about dangerousness being most common. The great majority (89.8%) had a diagnosis of schizophrenia. Discussion The development of a community mental health system and the introduction of a health insurance system in Aceh (together with the national health insurance scheme for the poor) has enabled access to free hospital treatment for people with severe mental disorders, including those who have been in pasung. The demographic and clinical characteristics of this group of ex-pasung patients are broadly similar to those reported in previous studies. Conclusions The Aceh Free Pasung program is an important mental health and human rights initiative that can serve to inform similar efforts in other parts of Indonesia and other low and middle-income countries where restraint and confinement of the mentally ill is receiving insufficient attention.